2014
DOI: 10.1175/jtech-d-13-00083.1
|View full text |Cite
|
Sign up to set email alerts
|

In situ Quality Assessment of a Novel Underwater pCO2 Sensor Based on Membrane Equilibration and NDIR Spectrometry

Abstract: The final published version of this manuscript will replace the preliminary version at the above DOI once it is available.If you would like to cite this EOR in a separate work, please use the following full citation:Fietzek, P., B. Fiedler, T. Steinhoff, and A. Körtzinger, 2013: In situ quality assessment of a novel underwater pCO2 sensor based on membrane equilibration and NDIR spectrometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(85 citation statements)
references
References 29 publications
2
83
0
Order By: Relevance
“…During that comparison, all sensors showed increasing offsets with time compared to GO (from 15 to 60 μ atm), which emphasized the challenges of intercomparison exercises with longer duration and showed the unknown, and possibly limited endurance of unattended systems. The increasing offsets reflected sensor drift, and laboratory postdeployment calibration of the sensors permitted drift‐corrections (Fietzek et al ) so that comparison of final corrected data showed agreement with GO that was comparable to the results from this study, showing the importance of applying proper procedures, such as drift corrections, to improve data quality. Furthermore, short‐term drifts in the IR cells within each zeroing/spanning cycle must be accounted for, and it is important to note that each system performs different drift corrections (e.g., CO2‐Pro only performs a zero point calibration).…”
Section: Discussionsupporting
confidence: 79%
“…During that comparison, all sensors showed increasing offsets with time compared to GO (from 15 to 60 μ atm), which emphasized the challenges of intercomparison exercises with longer duration and showed the unknown, and possibly limited endurance of unattended systems. The increasing offsets reflected sensor drift, and laboratory postdeployment calibration of the sensors permitted drift‐corrections (Fietzek et al ) so that comparison of final corrected data showed agreement with GO that was comparable to the results from this study, showing the importance of applying proper procedures, such as drift corrections, to improve data quality. Furthermore, short‐term drifts in the IR cells within each zeroing/spanning cycle must be accounted for, and it is important to note that each system performs different drift corrections (e.g., CO2‐Pro only performs a zero point calibration).…”
Section: Discussionsupporting
confidence: 79%
“…For example, Degrandpre et al () demonstrate a SAMI‐CO 2 accuracy/precision of ± 2 μatm and ± 1 μatm, respectively, although an intercomparison with a NDIR‐based equilibrator system resulted in an overall offset between the two systems of 3.7 μatm. In comparison to a NDIR‐based equilibrator system, Fietzek et al () found a Contros Hydro‐C offset and precision of −0.6 μatm and ± 3 μatm, respectively. However, after careful characterization against a validation system the SIPCO2 sensor performance is comparable to that of some of the systems presented in Table .…”
Section: Discussionmentioning
confidence: 99%
“…The HydroC sensor was serviced and calibrated yearly by Contros. The relative standard deviation (RSD) of the pCO 2 measurement has been estimated to be 1 % (Fietzek et al, 2014).…”
Section: Datamentioning
confidence: 99%